Gut mycobiome: The probable determinative role of fungi in IBD patients. Issue 5 (3rd February 2021) - Beheshti‐Maal, Alireza; Shahrokh, Shabnam; Ansari, Saham; Mirsamadi, Elnaz Sadat; Yadegar, Abbas; Mirjalali, Hamed; Zali, Mohammad Reza
Abstract: Inflammatory bowel disease (IBD) is a multi‐factorial autoimmune disorder that its causative agents are unknown. The gut microbiota comprises of bacteria, viruses, fungi and protozoa that its role in IBD has remained controversially. Bacteria constitute more than 99% of the gut microbiota composition, and the main core of the gut microbiota is composed from Bacteroidetes and Firmicutes . The gut microbiota plays an important role in training, development and haemostasis of the immune responses during the life. Fungi compose a very small portion of gut microbiota, but play determinative roles in homeostasis of the gut bacterial composition and the mucosal immune responses. An interkingdom correlation between bacteria and fungi has been suggested. For example, the presence of Salmonella enterica serovar Typhimurium reduces the viability and colonisation of C albicans . Alterations in the composition and function of the gut microbiota, which is known as dysbiosis, are a usual event in patients who suffer from IBD. Although the main reason for this alteration is not clear, the interaction between gut bacteria and gut fungi seems to be an important subject in IBD patients. This review covers new findings on the interaction between fungi and bacteria and the role of fungi in the pathophysiology of IBD.